2016
DOI: 10.5539/gjhs.v8n9p91
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stress Management on Occupational Stress and Satisfaction among Midwives in Obstetrics and Gynecology Hospital Wards in Iran

Abstract: Introduction:Occupational stress is one of the major problems of health care staff, substantially affecting their professional and personal performance. This research has been conducted with the aim of determining the effect of stress management on occupational stress and satisfaction among the Midwives in Obstetrics and Gynecology Hospital wards at Motahari Hospital in Jahrom, Iran 2013-2014.Methods:This is a Quasi-experimental study of the pre- and post-clinical trials type. The study population included mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Both scales demonstrated acceptable validity and reliability. The study results indicated that the intervention group showed mitigated stress but there was no increase in job satisfaction as compared to controls . The authors noted that the initial effects of the program were not sustainable at the one‐month postintervention point …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Both scales demonstrated acceptable validity and reliability. The study results indicated that the intervention group showed mitigated stress but there was no increase in job satisfaction as compared to controls . The authors noted that the initial effects of the program were not sustainable at the one‐month postintervention point …”
Section: Resultsmentioning
confidence: 95%
“…The second quantitative study included 70 midwives in an Iranian hospital . This quasi‐experimental study included one control and one intervention group, each with 35 midwives, and evaluated midwives’ general occupation stress and job satisfaction after participation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Karimyar Jahromi et al (19) evaluated the impact of stress management program on occupational stress in 35 midwives. The results showed that short-term training workshop of stress management caused a significant reduction in the mean score of occupational stress in the intervention group compared to the control group, which is consistent with the present study findings.…”
Section: Discussionmentioning
confidence: 99%